Practical Pollution-Routing problem with time-dependent speeds: insights from São Paulo. - Santos, Luiz Felipe de Oliveira Moura (2019)
Vehicle routing problems (VRP) are one of the most studied problems in combinatorial optimization. In recent years, it has gained the attention of many researchers and business organizations not only in its classical application, but also because of the many environmental considerations that it is possible to consider. Objectives that aims to reduce fuel consumption or directly the emissions of CO2 and other greenhouse gases (GHG) have become widely adopted. Being so, many models that estimate emissions and fuel consumption have been proposed in the literature, accounting for different factors that affect fuel consumption in road transportation, such as payload, slope and travel speed. These comprehensive models, while providing very accurate results in modeling emissions and fuel consumption, are very dependent on numerous parameters and user inputs, many not easily retrievable by practitioners. In this way, a Practical Pollution-Routing Problem (PPRP) is a VRP that aims to reduce fuel consumption using simple and practical computations based on the Fuel Consumption Rate (FCR) of vehicles. Another important variant of the VRP that has also attracted recent attention is the time-dependent vehicle routing problem (TDVRP), in which the effects of congestion and travel speeds fluctuations during the day are taken into account when designing the delivery routes. A time-dependent approach to the PPRP, however, has not been found in the literature. Thus, our research addresses this gap and aims to propose a new variant of this problem called the Practical Pollution-Routing Problem with Time-Dependent speeds (PPRP-TD), as it has important value to practitioners interested in the reduction of fuel consumption and the hazardous effects caused by diesel trucks. We propose several instance problems based on real operations of a major retailer company that distributes in São Paulo, and also analyze the time dependent speeds of the São Paulo network. To solve both the PPRP and the PPRP-TD, we propose the GRASP-FESA solution method, which is an FCR-based Extended Savings Algorithm (FESA) combined with a Greedy Randomized Adaptive Search Procedure (GRASP) metaheuristic. In the case of the PPRP-TD, we also perform an extensive time-dependent scheduling for all given routes. The method is able to provide good results, although being computationally expensive in the case of large instances.